P092 Herpes simplex virus type 1 epidemiology in latin america and the caribbean: systematic review and meta-analytics. (14th July 2019) - Sukik, Layan; Alyafei, Mariam; Harfouche, Manale; Abu-Raddad, Laith
Abstract : Background: We aim to investigate the epidemiology of herpes simplex virus type 1 (HSV-1) in Latin America and the Caribbean. Methods: Systematic review and meta-analytics guided by the Cochrane Collaboration Handbook and reported following the PRISMA guidelines. Results: Thirty-one relevant reports were identified including 35 overall (and 95 stratified) seroprevalence measures, and five and seven proportions of virus isolation in genital ulcer disease (GUD) and in genital herpes, respectively. Pooled mean seroprevalence was 57.2% (95% CI: 49.7–64.6%) among children and 88.4% (95% CI: 85.2–91.2%) among adults. Pooled mean seroprevalence was lowest at 49.7% (95% CI: 42.8–56.6%) in those aged ≤10, followed by 77.8% (95% CI: 67.9–84.8%) in those aged 10–20, 82.8% (95% CI: 73.1–90.8%) in those aged 20–30, 92.5% (95% CI: 89.4–95.1%) in those aged 30–40, and 94.2% (95% CI: 92.7–95.5%) in those aged ≥40. Age was the strongest source of heterogeneity in seroprevalence, explaining 54% of variation. Evidence was found for seroprevalence decline over time. Pooled mean proportion of HSV-1 isolation was 0.9% (95% CI: 0.0–3.6%) in GUD and 11.1% (95% CI: 3.1–22.3%) in genital herpes. Conclusion: HSV-1 is a widely prevalent infection in this region, but its epidemiology appears to be slowly transitioning, with still limited contribution for HSV-1 in genital herpes. Disclosure: No significant relationships.